An evaluation on effects of surface explosion on underground tunnel; availability of ABAQUS Finite element method - Keskin, Inan; Ahmed, Mohammed Yadgar; Taher, Nichirvan Ramadhan; Gor, Mesut; Abdulsamad, Balen Zrar (Pergamon-Elsevier Science Ltd, 2022)
Tunnels are a paramount infrastructure due to the vast array of their uses. Despite all the safety measures taken during the design stages, tunnels still possess the weakness of being vulnerable to the effect of ground surface explosions, as the impact of such events can potentially cause the collapse of the whole structure, or parts of it, and hence leads to loss of lives. This paper utilizes Finite Element Methods (FEM) by using Abaqus/CAE software to examine the behavior of the underground circle-shaped tunnel when subjected to an impact load generated by ground-surface explosions. First, the FEM model was validated using the results of the experimental results available in the literature. After obtaining a reasonable agreement between the results of the FEM simulation and the experimental test model, then the software was used to determine the effect of the ground-surface explosion on an underground circle-shaped tunnel. The results exhibited that there is a good agreement between the surface crater size of the validation model and the crater size of the experimental test. Moreover, the intensity of explosion pressure on subsurface soil of the validation model on FEM gives the same result as obtained from the experimental test. The FEM simulation result indicated that the concrete lining and embedded steel rebar cage of the tunnel attain almost the same pressure profiles during the explosion period. In addition, air pressure was increased during the explosion period, which is in agreement with what has been proven in the literature.
Keywords: Finite Element Method; Abaqus; CAE; Circle-Shaped Tunnel; Explosions and TNT